MicroRNA-497 increases apoptosis in MYCN amplified neuroblastoma cells by targeting the key cell cycle regulator WEE1. - RYAN, JACQUELINE (My University, 2013)
Neuroblastoma is responsible for 15% of all childhood cancer deaths. Despite advances in treatment and disease management, the overall 5-year survival rates remain poor in high-risk disease (25-40%). MiR-497 was previously identified by our laboratory as a member of a miRNA expression signature, predictive of neuroblastoma patient survival and has been reported as a tumor suppressor in a variety of other cancers. WEE1, a tyrosine kinase regulator of the cell cycle and predicted target of miR-497, has emerged as an oncogene in several cancer types and therefore represents an attractive potential target for novel therapy approaches in high-risk neuroblastoma. Our aim was to investigate the potential tumor suppressive role of miR-497 in high-risk neuroblastoma. METHODS: Expression levels of miR-497 and WEE1 in tissues and cells were determined using RT-PCR. The effect of miR-497 and siWEE1 on cell viability was evaluated using MTS assays, apoptosis levels were determined using FACS analysis of Annexin V/PI stained cells, and target protein expression was determined using western blot. Luciferase reporter plasmids were constructed to confirm direct targeting. Results were reported as mean±S.E.M and differences were tested for significance using 2-tailed Students t-test. RESULTS: We determined that miR-497 expression was significantly lower in high-risk MYCN amplified (MNA) tumors and that low miR-497 expression was associated with worse EFS and OS in our cohort. Over-expression of miR-497 reduced cell viability and increased apoptosis in MNA cells. We identified WEE1 as a novel target for miR-497 in neuroblastoma. Furthermore, our analysis showed that high WEE1 levels are significantly associated with poor EFS and OS in neuroblastoma and that siRNA knockdown of WEE1 in MNA cell lines results in significant levels of apoptosis, supporting an oncogenic role of WEE1 in neuroblastoma. Cisplatin (CDDP) treatment of both miR-497 over-expressing cells and WEE1 inhibited cells, resulted in a significant increase in apoptosis in MNA cells, describing a synergistic effect and therefore a potential therapeutic for high-risk neuroblastoma. CONCLUSION: Our study's results are consistent with miR-497 being a candidate tumor suppressor in neuroblastoma, through the direct targeting of WEE1. These findings re-enforce the proposal of WEE1 as a therapeutic target in neuroblastoma.
PUBLISHED
Keywords: Neuroblastoma